Pressure dependent structural and optical properties of silicon carbide thin films deposited by hot wire chemical vapor deposition from pure silane and methane gases - Shariatmadar Tehrani, F.; Goh, B.T.; Muhamad, M.R.; Rahman, Saadah Abdul (Springer, 2012)
Silicon carbide (SiC) thin films were deposited using hot wire chemical vapor deposition technique from silane (SiH 4) and methane (CH 4) gas precursors. The effect of deposition pressure on structural and optical properties of SiC films was investigated. Various spectroscopic methods including Fourier transform infrared spectroscopy, Raman scattering spectroscopy, Auger electron spectroscopy, and UV-Vis-NIR spectroscopy were used to study these properties. Films deposited at low deposition pressure were Si-rich, and were embedded with nano-crystals of silicon. These films showed strong absorption in the visible region and had low energy band gaps. Near stoichiometric SiC film, were formed at intermediate deposition pressure and these films were transparent in the visible region and exhibited a wide optical band gap. High deposition pressures caused inhomogeneity in the film as reflected by the increase in disorder parameter and low refractive index of the films. This was shown to be due to formation of sp 2 carbon clusters in the film structure. Â© 2012 Springer Science+Business Media New York.